MP09: Predictors of return acute asthma visits among patients receiving guideline recommended discharge management in the emergency department. (May 2020) - Dhaliwal, C.; Haji, T.; Leung, G.; Madhura, T.; Giangioppo, S.; Radhakrishnan, D.
Abstract : Introduction: Despite improvements in the recognition of asthma among the pediatric population and the use of preventative therapies, rates of emergency department (ED) visits and hospitalizations remain high, leading one to question how these acute health care visits for asthma can be further avoided. In this study, we aimed to identify predictors of future repeat acute care visits among children and adolescents who had already received 'best practice' discharge treatments and instructions during their first asthma ED visit. Methods: We performed a retrospective single center cohort study of all children ages 1-17 years presenting to the ED at the Children's Hospital of Eastern Ontario in Ottawa, Canada for an acute asthma exacerbation during a 1-year time frame between September 1, 2014 – August 31, 2015. Only children with no prior ED asthma visit and documentation of receipt of a prescription for inhaled corticosteroids and/or a written asthma action plan were included. Multivariable logistic regression was performed to identify predictors of repeat future asthma ED visit or hospitalization in the year following the first ED visit. Results: We identified 909 children with an eligible ED visit during the study period, of whom 24% had a repeat asthma ED visit or hospitalization within the subsequent 1 year. Predictors of repeat acute asthma visits included having a nut allergy (OR 1.76, 95% CI: 1.15, 2.70), higher severity symptoms at triage (OR 2.04, 95% CI: 1.23, 3.39), a primary care physician (OR 2.23, 95% CI: 1.26, 3.93), or a prior history of asthma (OR 1.53, 95% CI: 1.03, 2.28). Conclusion: In children and adolescents with repeat asthma ED visits and hospitalizations despite having received 'best practice' asthma discharge management at their first ED visit, factors such as having an allergy to nuts, higher severity symptoms at presentation, a prior history of asthma, and having a primary care provider may be used to identify these more high-risk children and adolescents. Such parameters can be used practically to target and apply more intensive preventative interventions to those most in need at the first ED visit, in order to prevent future return visits.